THE INFLUENCE OF WORK MOTIVATION AND DISCIPLINE ON EMPLOYEE PERFORMANCE AT BANK BNI AMPERA BRANCH JAKARTA - Prasetyo Kurniawan; Priehadi Dhasa Eka; Henni Marlinah (Asosiasi Dosen Muda Indonesia, 2024)
This research aims to evaluate the impact of motivation and work discipline on employee performance at PT Bank Negara Indonesia (Persero) Tbk Ampera Branch, South Jakarta. The method was quantitative, with a sampling technique using saturated sampling, resulting in 75 respondents. Data analysis includes validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The research results show that motivation has a significant influence on employee performance. Likewise, work discipline also has a significant influence on employee performance. Simultaneously, motivation and work discipline significantly affect employee performance, with the regression equation Y = 7.274 + 0.402X1 + 0.438X2. The coefficient of determination reached 65.3%, while other factors influenced the remaining 34.7%.